Towards an Open Science-Based Framework for Software Engineering Controlled (Quasi-)Experiments - Cordeiro, André F. R.; OliveiraJr, Edson; Capretz, Luiz Fernando (Anais do Brazilian e-Science Workshop (BreSci), 2022)
Experimental Software Engineering has straightforwardly evolved in the last decades due to the effort of the community in providing consolidated training, teaching and practice. Particularly, for controlled experiments and quasi-experiments, the software engineering community has discussed on the lack of reproducibility and the missing of experimental artifacts sharing policies, such as, dataset, baselines, metamodels, repositories, and scripts. These are, therefore, important issues that jeopardizes controlled experimentation to evolve as rigorous as in millennial sciences as Medicine and Physics. In this ongoing work, it is presented a proposal of a conceptual framework for software engineering controlled experiments and quasi-experiments based on the main principles and practices of Open Science. It is understood that Open Science is one of the pillars to the evolution of science, consequently, to software engineering. The FAIR data, metadata, repositories, curation and provenance are some of the main practices discussed in this paper. Ongoing activities are described, in terms of how they are being performed and their relationship with prospective ones.